An experimental study on the yield strength of cement grout for grouting in the limestone area of a coal seam floor - Jun ZOU; Yan GUO; Herong GUI; Weimin WANG; Zhenlin CHEN; Faming LIU; Yanan DAI; Yang HU; Zengbao CHEN; Jun LI; Chuan GAO; Heng LI (Meitian dizhi yu kantan)
Objective and MethodsIn recent years, regional grouting through ground directional drilling has become the preferred technique for water disaster prevention and control in floor limestones in a coal mining area. In grouting engineering, the diffusion radius of cement grout, which has always received wide attention, is constrained by multiple factors including the shear yield strength (yield strength for short) and specific gravity of cement grout, along with grouting pressure. The diffusion radius in turn influences the implementation effects of on-site grouting engineering. Among its controlling factors, the yield strength of cement grout cannot be tested on site. Given this, this study investigated actual grouting conditions in the Hengyuan Coal Mine of the Huaibei coalfield. Using shear experiments on the prepared cement grout with varying specific gravities, this study analyzed the impacts of factors such as initial viscosity and setting time and determined the yield strength of the cement grout. Furthermore, it explored the impacts of the yield strength on factors like the diffusion radius of cement grout and grouting pressure. Results and ConclusionsThe results indicate that as the initial setting time increased, the initial viscosity of cement grout with specific gravities ranging from 1.2 to 1.6, prepared using cement P.O42.5 in the Hengyuan Coal Mine, increased with the specific gravity generally. Furthermore, a higher specific gravity corresponded to more rapid growth in the viscosity. The cement for regional grouting exhibited shear stresses ranging between 0 Pa to 17 Pa and yield strength from 0 Pa to 13 Pa before the initial setting. The cement grout with specific gravities of 1.2 and 1.3 was more prone to flow, thus suitable for grouting in narrow, deep microfractures in the third dolomite layer of the Taiyuan Formation. Under identical grouting conditions, the diffusion range of the cement grout decreased with an increase in its yield strength. Specifically, the diffusion range exceeded 35 m under a yield strength of 0.5 Pa while beginning to fall below 10 m in the case of yield strength greater than 1.5 Pa. Tracer tests verified that during grouting, the cement at a long diffusion distance originated primarily from the low-yield-strength cement grout with a low specific gravity of 1.2. This finding is consistent with the laboratory experiments. This study can serve as a reference for the implementation of grouting treatment engineering.